HARMONIC LINEARIZATION OF AUTOMATIC CONTROL SYSTEMS, CONTROLLED BY FINITE AUTOMATON UNDER THE IMPACT OF PARAMETRIC PERTURBATIONS - Yukhymhuk-Voytko, Marija (Scientific Works of Vinnytsia National Technical University, 2015)
Analytical dependences, which allow to perform harmonic linearization of systems, controlled by a finite automaton, under the impact of parametric perturbations, which lead to change, over time, of the parameters of nonlinear elements are determined. REFERENCES 1 Никифоров В. О., Ушаков А. В. Управление в условиях неопределенности: чувствительность, адаптация, робастность. – СПб.: СПбГИТМО (ТУ), 2002. – 232 с. 2. Дорф Р., Бишоп Р. Современные системы управления. – М.: Лаб. баз. знаний, 2002. – 832 с. 3 Гельднер К., Кубик С. Нелинейные системы управления. – М.: Мир,1987. – 368 с. 4. Быкова Г. М. Метод обобщенной гармонической линеаризации по k-й гармонике при исследовании динамических характеристик нелинейных систем // Изв. вузов. Приборостроение. – 1990. – № 1. – С. 80 – 85 5. Старикова М. В. Исследование автоматических систем с логическими управляющими устройствами. – М.: Машиностроение, 1987. – 224 с. 6. Юхимчук С. В. Узагальнення методу описуючих функцій для неоднозначних нелінійних нестаціонарних систем // Вісник Вінницького політехнічного інституту. – 1997. – №4. – С. 5 – 9.